Functional differences in upper limb movement after early and chronic stroke based on kinematic motion indicators - Monika Blaszczyszyn (Biomedical Papers, 2018)
Aims: The main purpose of this study was to determine the changes in kinematic parameters of ischemic stroke affected upper limbs, during simple functional activity, to determine the most relevant changes. Methods: The OptiTrack system was used for motion capture. To determine upper extremity function in Activities of Daily Living (ADL) tasks. During particular phases, the following matrices were chosen: mean and peak speed, normalized movement unit, normalized jerk and phase movement time. The chosen matrices represent the speed and smoothness profile of end-point data. The the arm-trunk compensation was also taken into consideration. Twenty stroke patients, in early (G1 from 1 to 3 months after stroke) and chronic stage (G2 from 6 months to 1 year), were studied. The large and small cylinder forward and back transporting phases were evaluated. Results: The most significant differences between groups G1 and G2 were in mean and peak speed of the forward transport of the large and small cylinders for the paretic limb. Significant differences were also found for the smoothness (measured by movement unit, mean and peak speed and jerk) where the G2 group had a rougher motion. There were also differences in arm-trunk compensation in the frontal plane. Conclusion: The variables used in the study showed applicability in assessing kinematic parameters in both the early and chronic period after stroke.